Developing a math textbook using realistic mathematics education approach to increase elementary students’ learning motivation - Jesi Alexander Alim; Neni Hermita; Melvi Lesmana Alim; Tommy Tanu Wijaya; Jerito Pereira (Jurnal Prima Edukasia, 2021)
This study aims to develop an appropriate and practical math textbook in the unit of the Least Common Multiple (LCM) and the Greatest Common Divisor (GCD) using Realistic Mathematics Education (RME) in order to increase elementary students’ learning motivation. This is a Research and Development (RnD) type of study with the Plomp model. A mathematician and a teacher assessed the validity of the textbook. The practicality of the textbook was assessed by two teachers and 15 students using questionnaires. The students' motivation was assessed by the students using questionnaires as well. The results showed that the textbook was appropriate with an average of 83.32%, the respondent results from the students’ views were practical with an average of 82.33% and very practical with an average of 87.6 from the teachers’ view. This study also found that the textbook increased the students’ learning motivation by 6.45%.